The turning of the year - Martin, Bill, 1916-2004.; Shed, Greg (San Diego : Harcourt Brace, 1998)
Describes the characteristics of each month in rhyming text and illustrations.
Kirkus Review.
L.A. Recommended Foreign Language.
School Library Journal.
4.2
K-3
Keywords: Months -- Fiction; Stories in rhyme; Months -- Fiction; Stories in rhyme